1880 Dakota Terr. Rev. Codes 771, Penal Code, ch. 23, §§ 295-295 - (:unkn) unknown (General Publisher, 1877)
A duel is any combat, with deadly weapons, fought between two persons by previous agreement or upon a previous quarrel. § 295. Punishment for Fighting. Every person guilty of fighting any duel, although no death or wound ensues, is punishable by imprisonment in the territorial prison not exceeding ten years.
--
Keywords: DEFINITIONS; DUELING